An active polarization-insensitive ultrathin metamaterial absorber with frequency controllability - Prakash; Agarwal M.; Meshram M.K. (My University, 2025)
In this paper, the design and simulated characteristics of the ultrathin square-shaped active metamaterial absorber are investigated. The unit cell of the proposed absorber is a fourfold symmetric structure consisting Jerusalem cross mounted with four pin diodes within the square ring. By switching the four diodes ON/OFF all at a time, the response of absorbance of this metamaterial structure switches from single-band to dual-band with polarization-insensitive characteristic. © Springer Nature Singapore Pte Ltd. 2019.